Disciplining the empire : politics, governance, and the rise of the British navy - Kinkel, Sarah, 1982- (Harvard historical studies ;, 2018)
"Rule Britannia! Britannia rule the waves" goes the popular lyric. The fact that the British built the world's greatest empire on the basis of sea power has led many to assume that the Royal Navy's place in British life was unchallenged. Yet, as Sarah Kinkel shows, the Navy was the subject of bitter political debate. The rise of British naval power was neither inevitable nor unquestioned: it was the outcome of fierce battles over the shape of Britain's empire and the bonds of political authority. Disciplining the Empire explains why the Navy became divisive within Anglo-imperial society even though it was also successful in war. The eighteenth century witnessed the global expansion of British imperial rule, the emergence of new forms of political radicalism, and the fracturing of the British Atlantic in a civil war. The Navy was at the center of these developments. Advocates of a more strictly governed, centralized empire deliberately reshaped the Navy into a disciplined and hierarchical force which they hoped would win battles but also help control imperial populations. When these newly professionalized sea officers were sent to the front lines of trade policing in North America during the 1760s, opponents saw it as an extension of executive power and military authority over civilians--and thus proof of constitutional corruption at home. The Navy was one among many battlefields where eighteenth-century British subjects struggled to reconcile their debates over liberty and anarchy, and determine whether the empire would be ruled from Parliament down or the people up.--